PENGARUH PROFITABILITAS, PERTUMBUHAN ASET, OPERATING LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL STUDI EMPIRIS PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Mega Junita; John G. Lumbanraja (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2019)
This study aims to analyze the influence of profitability, asset growth, operating leverage, and firm size of capital structure partially on food and beverages company listed on the Indonesia Stock Exchange. Independent variables used in this study are profitability, asset growth, operating leverage and firm size, while the dependent variable in this study is capital structure. Populations used in this study are food and beverages companies listed on IDX 2010-2012 where the total population is used by 18 companies. The sampling technique used was purvosive sampling technique in which the number of observations obtained this study was 54 (18x3). Test used in this study is the classical assumptions includes normality, heteroscedasticity, autocorrelation, and multicollinearity, and hypothesis test (t test and coefficients determination). Of the results of the testing that has been done, the partial regression test (t test) showed that the independent variables asset growth and operating leverage which has a significant influence on capital structure, while the independent variables profitability and firm size does not affect the capital structure.